Toxoplasmosis as a cause for behaviour disorders--overview of evidence and mechanisms - Fekadu, Abebaw; Shibre, Teshome; Cleare, Anthony J (Folia parasitologica, 2010)
BACKGROUND: There is growing interest in the role of microbial agents in the causation of psychiatric disorders. The neurotropic protozoan parasite Toxoplasma gondii is one of the main candidates and has been associated with various psychiatric conditions, including schizophrenia. METHODS: A narrative review of the literature from the main medical databases (Medline, PubMed, PsycINFO), Google Scholar and Google using combinations of applicable terms. RESULTS: T. gondii affects the brain in both the acute and the latent stages of infection causing apparent brain pathologies in infected rodents and both immuno-compromised and immuno-competent humans. In immuno-competent individuals, behavioural disorders are primarily related to the latent stages of the illness. Behavioural/mental disorders that include schizophrenia, mood disorders, personality changes and cognitive impairments may be related to infection with T. gondii. Evidence for a behavioural effect of T. gondii comes from observational reports in animal models and controlled behavioural analysis in humans. Indirect clues of infection also come from raised seroprevalence or serotitres of antitoxoplasma antibodies among those with mental disorders. The pathophysiologic mechanism through which T. gondii may exert its effect is not clear, but direct impact on the brain and changes in neuroimmunomodulation, neurotransmission and some gene-environment interactions are postulated. CONCLUSION: There is evidence supporting a potential role of T. gondii infection in the onset of some behavioural disorders. Confirmation of such a role would prove a significant breakthrough in the search for the aetiology, treatment and prevention of behavioural disorders, such as schizophrenia. However, the associations remain preliminary.
Keywords: Toxoplasmosis; toxoplazmóza; Mental Disorders; duševní poruchy; Humans; lidé